Cytoreductive nephrectomy in the era of targeted therapies: a review. (2nd May 2017) - Pindoria, Nisha; Raison, Nicholas; Blecher, Gideon; Catterwell, Rick; Dasgupta, Prokar
Abstract : In the pre‐targeted therapy era, palliative cytoreductive nephrectomy combined with cytokine immunotherapy was the standard treatment protocol for the management of metastatic renal cell carcinoma. The introduction of targeted therapies has improved response rates, median survival and overall prognosis when compared to immunotherapy. The role of cytoreductive nephrectomy in providing an independent survival advantage when used alongside immunotherapy has been demonstrated by two randomised controlled trials. However, with the new shift in improved treatment outcomes from cytokine immunotherapy to targeted therapies, the continuing role of cytoreductive nephrectomy as a viable surgical treatment method remains controversial.